Predictive and modifying factors of bone mineral density decline in patients with COPD. (March 2019) - Kameyama, Naofumi; Chubachi, Shotaro; Sasaki, Mamoru; Tsutsumi, Akihiro; Irie, Hidehiro; Sakurai, Kaori; Sayama, Koichi; Nakamura, Hidetoshi; Asano, Koichiro; Betsuyaku, Tomoko; Fukunaga, Koichi
Abstract: Rationale: Various determinants of osteoporosis have been previously identified. However, only a few longitudinal studies have examined related factors. We aimed to investigate factors predicting and modifying rapid decline of bone mineral density in patients with chronic obstructive pulmonary disease. Methods: We analyzed patients with chronic obstructive pulmonary disease whose bone mineral density were measured at least three times over three years (n = 111). We divided annual per cent changes of bone mineral density in different body parts into tertiles. Rapid decliners (n = 33) were defined as those with the largest decline in at least two parts; all other participants were defined as non-rapid decliners (n = 78). Results: At enrollment, bone mineral density did not differ between the two groups. However, rapid decliners had a significantly greater rate of new vertebral fractures over 3 years compared with non-rapid decliners. On multivariate logistic regression analysis, age, moderate to severe emphysema, no daily exercise habits, and anemia increased the likelihood of rapid decliners. Furthermore, patients who newly started and continued bisphosphonate exhibited higher annual per cent changes of bone mineral density than did those without bisphosphonate use. Conclusions: A rapid decline in bone mineral density correlates to a higher likelihood of vertebral fracture. We clarified the predictors of bone mineral density decline and demonstrated that bisphosphonate use might modify bone mineral density in patients with chronic obstructive pulmonary disease. Highlights: Factors predicting and modifying rapid decline of bone mineral density in COPD patients were investigated. Rapid decliners had a significantly greater rate of new vertebral fractures. Age, emphysema, no daily exercise habits, and anemia increased the likelihood of rapid decliners. Bisphosphonate had positive effect on BMD decline over 3 years.